Speckle Reduction in Projection Systems - Riechert, Falko (KIT Scientific Publishing, 2009)
A speckle pattern is a quasi-random interference pattern which typically emerges when lasers are used as illumination sources in projection applications and which severely degrades the image quality. Since in most projection applications high speckle disturbance is not tolerable, speckle reduction is a major issue. This work gives an introduction into the theoretical description of speckle and investigates different practical methods for speckle reduction in laser projection systems.